S-Alkylated/aralkylated 2-(1H-indol-3-yl-methyl)-1,3,4- oxadiazole-5-thiol derivatives. 1. Synthesis and Characterization - Rubab, Kaniz; Abbasi, Muhammad A.; Rehman, Aziz-ur; Siddiqui, Sabahat Zahra; Akhtar, Muhammad Nadeem (Pharmacotherapy Group, 2016)
Purpose: To synthesize and characterize S-alkylated/aralkylated 2-(1H-indol-3-ylmethyl)-1,3,4- oxadiazole-5-thiol derivatives. Methods: 2-(1H-indol-3-yl)acetic acid (1) was reacted with absolute ethanol and catalytic amount of sulfuric acid to form ethyl 2-(1H-indol-3-yl)acetate (2) which was transformed to 2-(1H-indol-3- yl)acetohydrazide (3) by refluxing with hydrazine hydrate in methanol. Ring closure reaction of 3 with carbon disulfide and ethanolic potassium hydroxide yielded 2-(1H-indol-3-ylmethyl)-1,3,4-oxadiazole-5- thiol (4) which was finally treated with alkyl/aralkyl halides (5a-u) in DMF and NaH to yield Salkylated/ aralkylated 2-(1H-indol-3-ylmethyl)-1,3,4-oxadiazole-5-thiols (6a-u). Structural elucidation was done by IR, 1H-NMR and EI-MS techniques Results: 2-(1H-indol-3-ylmethyl)-1,3,4-oxadiazole-5-thiol (4) was synthesized as the parent molecule and was characterized by IR and the spectrum showed peaks resonating at (cm-1) 2925 (Ar-H), 2250 (S-H ), 1593 (C=N ) and 1527 (Ar C=C ); 1H-NMR spectrum showed signals at δ 11.00 (s, 1H, NH-1ʹ), 7.49 ( br.d, J = 7.6 Hz, 1H, H-4'), 7.37 (br.d, J = 8.0 Hz, 1H, H-7'), 7.34 (br.s, 1H, H-2'), 7.09 (t, J = 7.6Hz, 1H, H-5'), 7.00 (t, J = 7.6 Hz, 1H, H-6') and 4.20 (s, 2H, CH2-10ʹ). EI-MS presented different fragments peaks at m/z 233 (C11H9N3OS)˙+ [M+2]+, 231 (C11H9N3OS)˙+ [M]+, 158 (C10H8NO)+, 156 (C10H8N2)˙+, 130 (C9H8N)+. The derivatives (6a-6u) were prepared and characterized accordingly. Conclusion: S-alkylated/aralkylated 2-(1H-indol-3-ylmethyl)-1,3,4-oxadiazole-5-thiols (6a-u) were successfully synthesized.